2022
DOI: 10.21203/rs.3.rs-2152556/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rickettsial DNA invasions and a scrambled rRNA cluster with a trans-splicing group I intron: The highly unorthodox mitogenome of the fern Haplopteris ensiformis

Abstract: Plant mitochondrial genomes can be complex owing to highly recombinant structures, lack of gene syntenies, heavy RNA editing and invasion of chloroplast, nuclear or even foreign DNA by horizontal gene transfer (HGT). Leptosporangiate ferns remained the last major plant clade without an assembled mitogenome, likely owing to a demanding combination of the above. We here present both organelle genomes of Haplopteris ensiformis as a first leptosporangiate fern. More than 1,400 events of C-to-U RNA editing and over… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Since the early days of molecular systematics, molecular phylogenetic studies in land plants have heavily relied on the plastid genome (plastome), due to its high copy number and more stable structure compared to the other two genomes (mitogenome and nuclear genome) (Zardoya 2020). Thanks to the high-throughput sequencing techniques, studies using the other two genomes have recently become more common, resulting in improved understanding of the evolution of plants and their genomes (e.g., Guo et al 2016, Jackman et al 2020, Kan et al 2020, Sullivan et al 2020, Zardoya 2020, Feng & Wicke 2023, Zumkeller et al 2023. Whereas the plastome is structurally rather conserved, the plant mitogenome varies greatly in size, gene structure, mutation rate, and level of RNA editing, hampering its assembly and use in phylogenetic studies (Ogihara et al 2005, Richardson et al 2013, Bonavita & Rosaria 2016, Small et al 2020, Zardoya 2020, Zumkeller et al 2023.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the early days of molecular systematics, molecular phylogenetic studies in land plants have heavily relied on the plastid genome (plastome), due to its high copy number and more stable structure compared to the other two genomes (mitogenome and nuclear genome) (Zardoya 2020). Thanks to the high-throughput sequencing techniques, studies using the other two genomes have recently become more common, resulting in improved understanding of the evolution of plants and their genomes (e.g., Guo et al 2016, Jackman et al 2020, Kan et al 2020, Sullivan et al 2020, Zardoya 2020, Feng & Wicke 2023, Zumkeller et al 2023. Whereas the plastome is structurally rather conserved, the plant mitogenome varies greatly in size, gene structure, mutation rate, and level of RNA editing, hampering its assembly and use in phylogenetic studies (Ogihara et al 2005, Richardson et al 2013, Bonavita & Rosaria 2016, Small et al 2020, Zardoya 2020, Zumkeller et al 2023.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the high-throughput sequencing techniques, studies using the other two genomes have recently become more common, resulting in improved understanding of the evolution of plants and their genomes (e.g., Guo et al 2016, Jackman et al 2020, Kan et al 2020, Sullivan et al 2020, Zardoya 2020, Feng & Wicke 2023, Zumkeller et al 2023. Whereas the plastome is structurally rather conserved, the plant mitogenome varies greatly in size, gene structure, mutation rate, and level of RNA editing, hampering its assembly and use in phylogenetic studies (Ogihara et al 2005, Richardson et al 2013, Bonavita & Rosaria 2016, Small et al 2020, Zardoya 2020, Zumkeller et al 2023. Despite the highly variable structure of plant mitogenomes, it has been broadly demonstrated that mitochondrial genes in flowering plants have lower substitution rates than plastid genes (Wolfe et al 1987, Palmer & Herbon 1988, Cho et al 2004, Parkinson et al 2005, Richardson et al 2013, and that some species seem to have practically frozen mitogenome (Richardson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early days of molecular systematics, molecular phylogenetic studies in land plants have heavily relied on the plastid genome (plastome), due to its high copy number and more stable structure compared to the other two genomes (mitogenome and nuclear genome) (Zardoya 2020). Thanks to the high-throughput sequencing techniques, studies using the other two genomes have recently become more common, resulting in improved understanding of the evolution of plants and their genomes (e.g., Guo et al 2016, Jackman et al 2020, Kan et al 2020, Sullivan et al 2020, Zardoya 2020, Feng & Wicke 2023, Zumkeller et al 2023. Whereas the plastome is structurally rather conserved, the plant mitogenome varies greatly in size, gene structure, mutation rate, and level of RNA editing, hampering its assembly and use in phylogenetic studies (Ogihara et al 2005, Richardson et al 2013, Bonavita & Rosaria 2016, Small et al 2020, Zardoya 2020, Zumkeller et al 2023.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the high-throughput sequencing techniques, studies using the other two genomes have recently become more common, resulting in improved understanding of the evolution of plants and their genomes (e.g., Guo et al 2016, Jackman et al 2020, Kan et al 2020, Sullivan et al 2020, Zardoya 2020, Feng & Wicke 2023, Zumkeller et al 2023. Whereas the plastome is structurally rather conserved, the plant mitogenome varies greatly in size, gene structure, mutation rate, and level of RNA editing, hampering its assembly and use in phylogenetic studies (Ogihara et al 2005, Richardson et al 2013, Bonavita & Rosaria 2016, Small et al 2020, Zardoya 2020, Zumkeller et al 2023. Despite the highly variable structure of plant mitogenomes, it has been broadly demonstrated that mitochondrial genes in flowering plants have lower substitution rates than plastid genes (Wolfe et al 1987, Palmer & Herbon 1988, Cho et al 2004, Parkinson et al 2005, Richardson et al 2013, and that some species seem to have practically frozen mitogenome (Richardson et al 2013).…”
Section: Introductionmentioning
confidence: 99%